Nanostructures: a platform for brain repair and augmentation - Vidu, Ruxandra; Rahman, Masoud; Mahmoudi, Morteza; Enachescu, Marius; Poteca, Teodor D.; Opris, Ioan (Frontiers in Systems Neuroscience, 2014)
Nanoscale structures have been at the core of research efforts dealing with integration of nanotechnology into novel electronic devices for the last decade. For instance, the unique electrical and optical properties of nanowires, nanotubes and nanocables with vertical orientation, assembled in nanoscale arrays, have been used in many device applications such as sensors that hold the potential to augment brain functions. However, the challenge in creating nanowires/nanotubes or nanocables arrays based sensors lies in making individual electrical connections fitting both the features of the brain and of the nanostructures. This review discusses two of the most important applications of nanostructures in neuroscience. First, the current approaches to create nanowires and nanocable structures are reviewed to critically evaluate their potential of developing unique nanostructure based sensors to improve recording and device performance to reduce noise and the detrimental effect of the interface on the tissue. Second, the implementation of nanomaterials in neurobiological and medical applications will be considered from the brain augmentation perspective. Because the size of nanomaterials is of the same order of magnitude with that of biomolecules, these materials are valuable tools for nanoscale manipulation in a broad range of neurobiological systems. Novel applications for diagnosis and treatment of brain diseases such as multiple sclerosis, meningitis, stroke, epilepsy, Alzheimer disease, schizophrenia, and autism will be considered. Because the blood brain barrier (BBB) has a defensive mechanism in preventing nanomaterials arrival to the brain, various strategies to help them to passing through the BBB will be discussed. The nanostructures at the interface between nanotechnology and neuroscience will play a pivotal role not only in addressing the multitude of brain disorders but also to repair/augment brain functions.